Exploring Cultural Representations in Regional Content on YouTube: A Comprehensive Review - Nursilah, Nursilah; Jayadi, Usman (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2025)
This study explores the representation of regional cultures on YouTube, highlighting how digital platforms serve as vital spaces for cultural expression, preservation, and dissemination. As a leading video-sharing platform, YouTube plays a crucial role in showcasing diverse cultural narratives and allowing users to engage with local traditions, customs, and lifestyles from around the world. Employing qualitative methods, including content analysis of selected videos and interviews with content creators, this research investigates how cultural elements are portrayed and perceived in the digital landscape. The findings reveal that YouTube not only democratizes access to cultural content but also facilitates cross-cultural exchanges, fostering understanding among diverse audiences. However, challenges related to authenticity, cultural commodification, and the potential loss of cultural integrity are evident, raising critical questions about the portrayal of local narratives in a global context. This study concludes that while YouTube presents significant opportunities for cultural representation, careful consideration is necessary to ensure the accurate and respectful conveyance of cultural identities. Recommendations for content creators and policymakers are provided to enhance the effectiveness of cultural representation and encourage responsible content creation in the digital age.